Indonesia’s Communication Study Paradigm (A Preliminary Study) - Nasucha, Muchammad; Turpyn, Juan M.F. (Jurnal Studi Jurnalistik, 2023)
The paradigm, the foundation and fundamental of science has been examined by scholars since the earliest period, also in communication studies. Referring to some authors, it is part of typologies that necessary to encompass when talking about scientific discipline particularly communication. However, the historical root of the studies is unavoidable evidences has significantly influenced the studies in world including Asian. Some authors have articulated their views regarding to the paradigm and its trivial in the discourse from the need for the studies until the theoretical perspectives and others. Nevertheless, Indonesia as one of the crucial countries in Asia apparently has not been studied widely and intensely. This paper tries to find how Indonesia's paradigm of communication studies that occured and have extended until nowadays, by tracing into many academic practices, in research papers that published through journals, books and educational institutions. Indonesian communication professor[s] as the figure[s] of the discipline considered as the authoritative sources to draw the discipline. Some [public] documents also show the empirical practice related to this matter. Finally, based on the data there are some conclusions designate that Indonesia paradigm of communication studies has been influenced by the Europe and US thought and tradition following the historical roots of the scholars who have studied in US, Europe, and Australia colleges. One of the perspectives about Indonesia’s communication theory is namely archipelago communication as part of Indonesian paradigm of communication study.